Clinical Techniques and Technology: Vestibular Telemetry. (2nd March 2021) - Phillips, John S.; Newman, Jacob L.; Cox, Stephen J.
Abstract : When a patient presents to a clinician with dizziness, it can be difficult for the patient to describe their symptoms in a clear manner, and clinical examination often yields entirely normal results. Ideally, it would be favorable to measure key physiological parameters during their episodes of dizziness. From a clinical perspective, this would allow a more timely and more accurate diagnosis. From a research perspective, it would allow a greater understanding of how the vestibular system malfunctions as a consequence of vestibular disease. The authors of this report have been funded by the UK Medical Research Council to develop and test a novel technology to measure, record, and analyze key physiological parameters provided by the dizzy individual during an episode of dizziness while active in the community. We provide the context to evolving work in this field, the outcome of preliminary studies, and a consideration of future opportunities.